Calidad del servicio a los usuarios de la papelería y librería amazonas del cantón Ventanas - Morales Montero, Jennifer Rosanna (2021)
This case study emphasizes the importance of quality of service and its repercussions on a certain company, it is in the public domain that today companies and businesses act in a dynamic and innovative way as a result of the great competencies existing in the market , and of course considering other variables that are highly demanded and incidents in this globalized world, therefore, the quality of the service is essentially based on an implicit tool in every organization that contributes to the satisfaction and loyalty of existing customers and to the retention of new, originates a beneficial value for the organization oriented to its permanence and growth in the market in which it competes. It is necessary to emphasize that the existence and longevity of the ideal commercial actions and effective human relations, implies the dedication and willingness of the collaborators, demonstrating a certain proactivity, in such a way that they lead to the desired goal, working in constant continuous improvement. In addition, many entrepreneurs do not obtain such profitability given that there are not those essential requirements for the correct functioning of their organization, thus deriving a low acceptance of customers and because of those gaps it has been necessary to determine and analyze them to provide a service quality that leads to the profitability that you want to achieve with those products that are marketed, that is, eradicating their shortcomings.